Analysis of Interaction Between Atmosphere and Sea Using The Delft3D Hydrodynamics Model for Mapping Coastal Flood Zone at Belawan Port and Coastal - Putra, Rizki Fadhillah Pratama; Nasution, Tulus Ikhsan; Humaidi, Syahrul; Darmawan, Yahya (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2023)
Belawan port and coastal areas were also not spared from the impact of the tidal flood. This study aims to determine the performance of the Delft3D hydrodynamic model in simulating sea level and waves in tidal floods at Belawan port and coastal area. Final operational global analysis data, MSLP data from NOAA/NCEP, and tidal data from ECMWF were used to run the Delft3D model. The model output was verified by using tide gauge observation data from BIG (Geospatial Information Agency). This research resulted in a mapping of areas affected by tidal flooding in the Belawan port and coastal area by analyzing the interaction between atmosphere, consisting of wind speed and direction parameters and sea parameters in the form of significant wave height. Based on the results of the Delft3D verification with observation data, the average error value is 23.5 cm and the coefficient of correlation is 0.93. This shows that the Delft3D model is quite good at simulating tidal flood heights in the Belawan port and coastal area. Based on atmospheric analysis, it does not really affect the increasing wave height. The influence is given by significant sea wave height, which can increase the height of tidal floods.